2017
DOI: 10.1088/1367-2630/aa7d6e
|View full text |Cite
|
Sign up to set email alerts
|

Linear response of zero-resistance states

Abstract: A two-dimensional electron system in the presence of a magnetic field and microwave irradiation can undergo a phase transition towards a zero-resistance state (ZRS). A widely used model predicts the ZRS to be a domain state, which responds to applied dc voltages or dc currents by slightly changing the domain structure. Here we propose an alternative response scenario, according to which the domain pattern remains unchanged. Surprisingly, a fixed domain pattern does not destroy zero-resistance, provided that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…At the same time, in many instances the observed cyclic voltage reversal was almost periodic in time which suggests a hidden slow deterministic dynamics favoring the reversal of field in domains. In other words, experiments indicated that the actual domain state in ZRS is not static in contrast to theoretical predictions [8][9][10][11][12][13][14][15][16] 1 .…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…At the same time, in many instances the observed cyclic voltage reversal was almost periodic in time which suggests a hidden slow deterministic dynamics favoring the reversal of field in domains. In other words, experiments indicated that the actual domain state in ZRS is not static in contrast to theoretical predictions [8][9][10][11][12][13][14][15][16] 1 .…”
mentioning
confidence: 63%
“…Here we address the dynamic properties of ZRS which are largely insensitive to the underlying nonequilibrium kinetics of electrons: at relevant large spatial and time scales the microscopic dynamics is fully encoded in local conductivity and diffusion coefficients which enter as phenomenological parameters into the classical equations of motion [5,[8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%